2018
DOI: 10.3389/fmicb.2018.01161
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Entomopathogenic Fungus Beauveria bassiana in the Rhizosphere of Wound-Stressed Zea mays Plants

Abstract: Entomopathogenic fungi from the genus Beauveria (Vuillemin) play an important role in controlling insect populations and have been increasingly utilized for the biological control of insect pests. Various studies have reported that Beauveria bassiana (Bals.), Vuill. also has the ability to colonize a broad range of plant hosts as endophytes without causing disease but while still maintaining the capacity to infect insects. Beauveria is often applied as an inundative spore application, but little research has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 73 publications
3
33
0
1
Order By: Relevance
“…Similarly, it was demonstrated that BbC1-inoculated Matina and Harzfeuer tomato plants displayed reduced growth effects as a result of infestation with the fall armyworm (unpublished report). Most probably, Bb acted as an antagonist against S. frugiperda larvae by producing metabolites that reduced insect infestations on their host plants (Jaber and Ownley 2018) or changed the plant defense responses and recruited Bb as a defensive strategy against insect herbivore (McKinnon et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was demonstrated that BbC1-inoculated Matina and Harzfeuer tomato plants displayed reduced growth effects as a result of infestation with the fall armyworm (unpublished report). Most probably, Bb acted as an antagonist against S. frugiperda larvae by producing metabolites that reduced insect infestations on their host plants (Jaber and Ownley 2018) or changed the plant defense responses and recruited Bb as a defensive strategy against insect herbivore (McKinnon et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of Beauveria inoculum in the rhizosphere of corn after 30 days was enhanced when plants were subjected to intensive wounding of foliage which crudely simulated herbivory. This was explained as a defence against insect herbivory that also has the result of promoting Beauveria colonization in the plant (McKinnon et al 68).…”
Section: Modulation Of Plant Defence Responsementioning
confidence: 99%
“…In this study, Metarhizium and Beuaveria were relatively abundant across all sampling sites. Prior studies that have laid emphasis on the ability of these generalist fungi to interact with plants, suggesting that the type of vegetation canopy may be associated with their widespread distribution in ecosystems (Wyrebek et al, 2011;Behie et al, 2012;Behie and Bidochka, 2013;Kepler et al, 2015;Keyser et al, 2015;McKinnon et al, 2017McKinnon et al, , 2018Tall and Meyling, 2018). Thus, based on the unique relationship of Metarhizium and Beauveria lineages with the plant rhizospheres, the high frequencies with which these are found in the forest habitats and the grassland habitats can be conceivably illustrated by adding an analysis of fungal-plant associations to the study.…”
Section: Discussionmentioning
confidence: 99%